Licenciatura híbrida em Matemática : quais são os papéis dos vídeos digitais? - Cunha, José Fernandes Torres da (2023)
The aim of this research is to analyze the role of digital videos in the hybrid undergraduate course in Mathematics at the State University of Mato Grosso (Unemat). The qualitative research takes place in the natural environment of Emergency Remote Teaching which included the virtual rooms of the Integrated System of Management of Academic Activities (SIGAA), the Google Meet and WhatsApp groups of the investigated discipline. The participants of the research were 11 professors and 46 students from two courses: Analytic and Vector Geometry (25) and Foundations of Elementary Mathematics (21). The data were produced by means of a questionnaire; semi-structured interviews; focus group; participant observation and analysis of the videos produced and used in the above mentioned courses. Due to the social isolation measures, adopted during the COVID-19 pandemic, all these procedures were carried out entirely online. The Activity Theory, the humans-with-media construct, and the notions of transformative agency and the agency of things were the theoretical frameworks that supported the data analysis of this research. Data analysis indicated that the agency (power of action) of SARS-CoV-2 impacted the network of activity systems during the research, as well as indicated the emergence of a process of ubiquitous agency, resulting from teachers’ and students’ coparticipative agency with digital videos. This process propelled movements in the activity systems that were established in the investigated disciplines. The results of this investigation further indicate that, digital videos expanded their natural role as artifact by playing the roles of subjects and community in the activity systems. By acting as agents (subjects), this media caused distinct movements in these systems, depending on their characteristics. The planned videos – video lessons produced by the professor and other videos available on YouTube – became mobilizing agents of classroom expansion. The spontaneous videos – videos produced without previous planning, resulting from synchronous interactions between professors and students – acted in the virtual presence of the professor, thus awakening in the students a sense of belonging, analogous to what occurs in the research community. This contributed to the students’ breaking through the fear of asking for help. By developing the notion of ubiquitous agency, this research presents theoretical elements that allow clarifying issues related to the place that media (specifically digital videos) occupy in the production of mathematical knowledge in collective humans-with-things.